The relationship between body measurements and performance traits of selected barrows carried to heavy weights - D H Carnahan; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1978)
Forty-seven Yorkshire barrows were selected for large and small scale test groups by using body height and length as a selection index. Initially the index between groups differed; however, the same measurements gave indexes that were nearly equal when the pigs weighed 210 and 300 lbs. Large scale barrows gained faster per day than did small scale barrows from start to 210 lbs; however, there were no differences in feed efficiency or backfat thickness. No differences were observed between scale groups fed to 300 lbs for the traits of average daily gain, feed efficiency, backfat thickness, carcass length, or loin eye area. Head measurements correlated poorly with performance and carcass traits. Pigs with the larger heartgirths and wider chests grew faster, but because they also had more backfat, they yielded a lower percentage of lean cuts. Pigs that had more bone and larger tail circumference and were longer tended to be the leaner pigs.; Swine Day, Manhattan, KS, November 9, 1978
Keywords: Swine day; 1978; Kansas Agricultural Experiment Station contribution; no. 79-105-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 342; Swine; Body measurements; Performance traits; Barrows; Scale groups